Oil painting step-by-step - Gregory, Noel; Horton, James; Lang, Roy; Sanders, Michael 1950- (Search Press Limited, 2020)
This is a practical and comprehensive guide for all oil painting enthusiasts, from the beginner to the experienced artist. Drawing on material previously published in the highly successful Leisure Arts series, four bestselling, professional artists provide advice on materials, painting from photographs, colour and composition. They describe basic and more advanced techniques such as wet on wet, wet on dry, scumbling, dry brush, sgraffito, impasto and glazing. For those wanting to avoid the use of additives like turpentine or white spirit, there is a section on water mixable oils. For readers who would like to see quick results, there is a section on instant oil painting, or painting in an intuitive, spontaneous way. Easy to follow step-by-step demonstrations show the reader how to paint landscapes, sea and sky, still life and flowers, and each section is accompanied by a selection of inspirational paintings by the four featured artists, in a rich variety of styles.